2006
DOI: 10.1123/ijsnem.16.6.620
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Amino Acid Supplementation on Muscle Soreness and Damage

Abstract: This study investigated the effect of a supplement containing 9 essential and 3 non-essential amino acids on muscle soreness and damage by comparing two endurance exercise bouts of the elbow flexors with amino acid or placebo supplementation in a double blind crossover design. The supplement was ingested 30 min before (10 h post-fasting) and immediately after exercise (Experiment 1), or 30 min before (2-3 h after breakfast), immediately post, and 8 more occasions over 4-day post-exercise (Experiment 2). Change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
105
2
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(121 citation statements)
references
References 23 publications
8
105
2
6
Order By: Relevance
“…Supplementation with BCAA (a combination of leucine, valine and isoleucine) both pre-and post-training has been shown to alleviate some of the symptoms most commonly associated with EIMD, including, serum CK levels [12], immediate-onset muscle soreness [13], reductions in muscle strength [14], as well as muscle catabolism [11]. Statistically significant results have been reported when supplementing varied dosages of BCAA alongside resistance training, from 3 g pre and post exercise to 20 g pre and post exercise [2,13,15].…”
Section: Introductionmentioning
confidence: 99%
“…Supplementation with BCAA (a combination of leucine, valine and isoleucine) both pre-and post-training has been shown to alleviate some of the symptoms most commonly associated with EIMD, including, serum CK levels [12], immediate-onset muscle soreness [13], reductions in muscle strength [14], as well as muscle catabolism [11]. Statistically significant results have been reported when supplementing varied dosages of BCAA alongside resistance training, from 3 g pre and post exercise to 20 g pre and post exercise [2,13,15].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that BCAA supplementation attenuates the increase in blood lactate dehydrogenase (Coombes et al, 2000;Koba et al, 2007) and creatine kinase (Coombes et al, 2000) after prolonged exercise. Another study has shown that supplementation with amino acids including BCAAs attenuates delayed-onset muscle soreness (Nosaka et al, 2006). These findings suggested that BCAAs attenuate the degree of exercise-induced muscle damage.…”
Section: Effects Of Amino Acid Supplementation On Patients With Copdmentioning
confidence: 82%
“…Various treatment strategies, including both physical interventions and pharmacological therapies, have been administered for prevention or reduction of DOMS and muscle damage and to enhance recovery from exercise-induced muscle damage (Howatson and van Someren, 2008). Although several nutritional supplement treatments have also been examined (Braun et al, 2005;Close et al, 2006;Cockburn et al, 2008;Etheridge et al, 2008;Lenn et al, 2002;Miller et al, 2004;Nosaka et al, 2006;Shimomura et al, 2006;White et al, 2008), the eŠectiveness of supplement intake has not been clearly demonstrated (Braun et al, 2005). However, some studies asserted Figure 1 Experimental design.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Nosaka et al (2006) found that continuous intake of amino acids following endurance exercise decreased DOMS and muscle damage. Intake of protein sources before and after exercise may attenuate exercise-induced muscle protein breakdown and stimulate muscle protein synthesis.…”
mentioning
confidence: 99%